Gender Responsiveness in the Management of Siargao Island Protected Landscape and Seascape (SIPLAS), Surigao Del Norte, Philippines - Reymark YBAÑEZ; Michael GALIGAO; Jay Mark CORTADO (International Journal of Environmental, Sustainability and Social Science, 2025)
This study assessed the level of gender responsiveness in the management of the Siargao Islands Protected Landscape and Seascape (SIPLAS) in Surigao del Norte, Philippines. Specifically, it examined the participation of men and women in management activities, identified gender-related issues, and evaluated existing programs supporting gender equality within the Protected Area Management Office (PAMO). Using a descriptive research design, data were collected through interviews and analyzed using frequency, percentage, and mean. Results revealed that women comprised 70% of the respondents, men 20%, and nonbinary individuals 10%, indicating strong female participation in administrative and technical roles, while men remained dominant in enforcement and field operations. Findings further showed that SIPLAS exhibits a moderately high level of gender responsiveness, with inclusive initiatives such as the celebration of Women’s Month, the collection of gender-disaggregated data, and gender-sensitive environmental training. However, gaps remain in the institutionalization of gender indicators and in the awareness of Republic Act 9710 (Magna Carta of Women), particularly among male staff. The study concludes that while PAMO demonstrates a growing commitment to gender equity and inclusivity, sustained institutional support, leadership balance, and continued gender sensitivity training are needed to achieve transformative and gender-equitable conservation governance in SIPLAS.